Data standards for heart failure: the European Unified Registries for Heart Care Evaluation and Randomized Trials (EuroHeart). (20th April 2022) - Aktaa, Suleman; Batra, Gorav; Cleland, John G F; Coats, Andrew; Lund, Lars H; McDonagh, Theresa; Rosano, Giuseppe; Seferovic, Petar; Vasko, Peter; Wallentin, Lars; Maggioni, Aldo P; Casadei, Barbara; et al.
Abstract: Standardized data definitions are essential for assessing the quality of care and patient outcomes in observational studies and randomized controlled trials. The European Unified Registries for Heart Care Evaluation and Randomized Trials (EuroHeart) project of the European Society of Cardiology (ESC) aims to create contemporary pan-European data standards for cardiovascular diseases, including heart failure (HF). We followed the EuroHeart methodology for cardiovascular data standard development. A Working Group including experts in HF registries, representatives from the Heart Failure Association of the ESC, and the EuroHeart was formed. Using Embase and Medline (2016–21), we conducted a systematic review of the literature on data standards, registries, and trials to identify variables pertinent to HF. A modified Delphi method was used to reach a consensus on the final set of variables. For each variable, the Working Group developed data definitions and agreed on whether it was mandatory (Level 1) or additional (Level 2). In total, 84 Level 1 and 79 Level 2 variables were selected for nine domains of HF care. These variables were reviewed by an international Reference Group with the Level 1 variables providing the dataset for registration of patients with HF on the EuroHeart IT platform. By means of a structured process and interaction with international stakeholders, harmonized data standards for HF have been developed. In the context of the EuroHeart, this will facilitate quality improvement, international observational research, registry-based randomized trials, and post-marketing surveillance of devices and pharmacotherapies across Europe. Graphical Abstract: Graphical Abstract EuroHeart: European Unified Registries for Heart Care Evaluation and Randomized Trials. Audio Abstract: